Pengaruh Pengunaan Media Pembelajaran IPA Berbasis Video terhadap Pengetahuan Siswa Sekolah Dasar - Aftania Tifani; Bintang Mahrani Abdullah; Fadhilah Hilmy Nasution; Pramudia Ananda; M Falih Daffa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is considered crucial in improving the quality of human resources, especially through the process of personal formation through education. Law Number 20 of 2003 concerning the national education system emphasizes the importance of a learning atmosphere and an active learning process. Teachers, especially in science learning, face challenges such as low motivation and lack of interest in the material.This research uses a quasi-experimental method to evaluate the effect of using video-based learning media on elementary school students' knowledge, especially in classifying animals. The research results show that video media is effective in increasing students' learning interest and motivation, facilitating understanding of abstract science concepts, and optimizing cognitive learning outcomes.It was found that learning with video media creates a fun, active and motivating learning atmosphere, contributing to the success of science teaching in fourth grade elementary school. The implications of this research indicate that the use of video media can be an effective solution in improving science learning at the elementary level, building students' interest in learning, and supporting their cognitive development.